Northern Young Contemporaries 1981 : An exhibition of recent work by art students throughout Great Britain. (Manchester : Whitworth Art Gallery, 1981)
Duncan, Diane ; Kasprzyk, Wladyslaw ; Lydiat, Anne ; Nicholson, David ; Schwab, Linda ; Walton, Gary
Northern Young Contemporaries 1981, Whitworth Art Gallery, Manchester, 7 November to 12 December 1981
boek